Răspunsuri

Cel mai inteligent răspuns!
2014-08-29T16:26:04+03:00
(1 + 3/2 - 5/2) : 6 - 1 = (2/2 + 3/2 - 5/2) : 6 - 1 = 0 : 6 - 1 = 0 - 1 =  -1
(12/35 - 7/20) * ( - 1 - 1/6) = (48/140 - 49/140) * (-6/6 - 1/6) = - 1/140 * (- 7/6) = 1/140 * 7/6 = 7/840 = 1/120
(6/32 + 5/24) * 30/38 - 1/8 = (18/96 + 20/96) * 30/38 - 1/8 = 38/96 * 30/38 - 1/8 = 30/96 - 1/8 = 15/48 - 1/8 = 15/48 - 6/48 = 9/48 = 3/16
3/4 - 1/12 - 1/4 - (4/3 - 1/2) = 2/4 - 1/12 - (8/6 - 3/6) = 6/12 - 1/12 - 5/6 = 5/12 - 5/6 = 5/12 - 10/12  = - 5/12
4/3 - 2/9 - ( 2 -3/4)  = 12/9 - 2 /9 - (8/4 - 3/4) = 10/9 - 5/4 = 40/36 - 45/36 = - 5/36
8/3 - (14/20 -1/15) : 3/10 - 8/15 = 8/3 - (42/60 - 4/60) : 3/10 - 8/15 = 8/3 - 38/60 : 3/10 - 8/15 = 8/3 - 38/60 * 10/3 - 8/15 = 8/3  - 380/180 - 8/15 = 480/180 - 380/180 - 96/180 = 
= 4/180 = 1/45
6/24 + 1/6 - (15/6 - 3) : 3/2 = 6/24 + 4/24 - (15/6 - 18/6) : 3/2 = 10/24 + 3/6 * 2/3 = 10/24 + 6/18 = 5/12 + 2/9 = 15/36 + 8/36 = 23/36
1 5 1